Lithosphere and upper-mantle structure of the southern Baltic Sea estimated from modelling relative sea-level data with glacial isostatic adjustment - H. Steffen; G. Kaufmann; R. Lampe (Solid Earth, 2014)
During the last glacial maximum, a large ice sheet covered Scandinavia, which depressed the earth's surface by several 100 m. In northern central Europe, mass redistribution in the upper mantle led to the development of a peripheral bulge. It has been subsiding since the begin of deglaciation due to the viscoelastic behaviour of the mantle. We analyse relative sea-level (RSL) data of southern Sweden, Denmark, Germany, Poland and Lithuania to determine the lithospheric thickness and radial mantle viscosity structure for distinct regional RSL subsets. We load a 1-D Maxwell-viscoelastic earth model with a global ice-load history model of the last glaciation. We test two commonly used ice histories, RSES from the Australian National University and ICE-5G from the University of Toronto. Our results indicate that the lithospheric thickness varies, depending on the ice model used, between 60 and 160 km. The lowest values are found in the Oslo Graben area and the western German Baltic Sea coast. In between, thickness increases by at least 30 km tracing the Ringkøbing-Fyn High. In Poland and Lithuania, lithospheric thickness reaches up to 160 km. However, the latter values are not well constrained as the confidence regions are large. Upper-mantle viscosity is found to bracket [2–7] × 10 20 Pa s when using ICE-5G. Employing RSES much higher values of 2 × 10 21 Pa s are obtained for the southern Baltic Sea. Further investigations should evaluate whether this ice-model version and/or the RSL data need revision. We confirm that the lower-mantle viscosity in Fennoscandia can only be poorly resolved. The lithospheric structure inferred from RSES partly supports structural features of regional and global lithosphere models based on thermal or seismological data. While there is agreement in eastern Europe and southwest Sweden, the structure in an area from south of Norway to northern Germany shows large discrepancies for two of the tested lithosphere models. The lithospheric thickness as determined with ICE-5G does not agree ...